1996
DOI: 10.1128/jcm.34.12.2897-2903.1996
|View full text |Cite
|
Sign up to set email alerts
|

Enteroadherent Escherichia coli and diarrhea in children: a prospective case-control study

Abstract: The relative contribution of diarrheagenic Escherichia coli was examined during a 1-year prospective study of hospitalized children in Clermont-Ferrand, France, including 220 case patients (with diarrhea) and 211 matched controls. Fecal isolates were characterized by means of their pattern of adherence to HEp-2 cells and by colony hybridization with DNA probes specific for the six categories of diarrheagenic E. coli. No enteroinvasive or enterotoxigenic E. coli isolates were isolated. Twenty-eight (6.5%) eae-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 55 publications
0
32
2
1
Order By: Relevance
“…It is tempting to propose that Afa/Dr DAEC is a "silent pathogen" that can emerge from the human intestinal microbiota. Indeed, it is intriguing that epidemiological studies have revealed that Afa/Dr DAEC strains may be regarded as resident colonic strains, since daaC-positive E. coli strains have been isolated with similar frequencies from patients and control subjects (127,167,356). The resident luminal bacteria seem to be an important factor in the development and chronicity of inflammatory bowel diseases, and an aggressive immunological response may be triggered by these bacteria rather than as a result of a change in the normal flora (261).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is tempting to propose that Afa/Dr DAEC is a "silent pathogen" that can emerge from the human intestinal microbiota. Indeed, it is intriguing that epidemiological studies have revealed that Afa/Dr DAEC strains may be regarded as resident colonic strains, since daaC-positive E. coli strains have been isolated with similar frequencies from patients and control subjects (127,167,356). The resident luminal bacteria seem to be an important factor in the development and chronicity of inflammatory bowel diseases, and an aggressive immunological response may be triggered by these bacteria rather than as a result of a change in the normal flora (261).…”
Section: Discussionmentioning
confidence: 99%
“…The first DNA probe, named daaC, was generated by Stapleton et al (413) and was a 300-bp PstI fragment of plasmid pSSS1 (daa operon), coding for part of an accessory protein of F1845 adhesin expressed by the diarrheagenic Afa/Dr DAEC C1845 strain (43). This DNA probe has been used in a large majority of the epidemiological studies of the association of Afa/Dr DAEC with diarrhea and urinary tract infections (1,5,68,112,127,130,131,141,143,152,208,209,256,257,293,329,344,364,366,367,400). Another constructed DNA probe, named drb (130), was a 260-bp PstI fragment of plasmid pIL14 (afa-1 operon) coding for the AfaE-I adhesin expressed by the uropathogenic Afa/Dr DAEC KS52 strain (243).…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations